Polymerized complex and electrodeposition synthesis of Ni-doped CuCo2O4 on flexible carbon fibers as a flexible electrocatalyst for oxygen evolution reaction - khongthon, Sirilak; Kiennork, Sert; Wongwanwattana, Pakawat; Sopunna, Kittichai; Yindeesuk, Anuwat; Chueachot, Romteera; Nakhowong, Ronariddh (Indochina Applied Sciences, 2023)
In this work, Ni-doped CuCo2O4 (Cu1–xNixCo2O4, x=0, 0.20, 0.40, 0.60 and 0.80) catalysts wer synthesized by polymerized complex and electrodeposition methods on flexible carbon fiber substrates for the oxygen evolution reaction (OER) in alkaline solution. The crystallinity and surface morphology of the catalysts were characterized by X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM).The XRD results showed that the crystallinity corresponded to CuCo2O4 phases. The OER revealed that Cu0.40Ni0.60Co2O4 had higher activity for OER with a low overpotential of 256 mV at a current density of 10 mA cm–2, which was better than CuCo2O4 (451 mV). The results suggest that the presence of Ni2+ ions in spinel CuCo2O4 exhibited superior electrocatalytic activity towards OER with lower overpotential, and higher current density than CuCo2O4.